Studies on the Effect of Urine on Biogas Production (Bangladesh Journal of Scientific and Industrial Research, 2007)
Only 20 % of our rural households in Bangladesh have more than 4 cattle heads and 21 % have more than 2 cattle heads. A 5-8 members family needs 4-6 cattle to run a biogas plant to meet their daily cooking energy. For wide spread dissemination of biogas technology throughout the country it becomes imperative to increase the number of biogas plant users by increasing the gas production rate with the present available cattle heads. It has been found that with the addition of urine to cow-dung gas production has been increased up to 30 % at a proportion of dung, urine and water (50:35:15) which will reduce the number of cattle heads and plant size and hence the construction cost. This will certainly increase the technology users up to 41 % with the present available cattle heads and thereby solve the cooking fuel and organic fertilizer crisis and maintain the hygienic condition. Bangladesh J. Sci. Ind. Res. 41(1-2), 23-32, 2006